The Involvement of the Androgen Receptor in the Secretion of the Epididymal corpus in the Lizard Podarcis sicula - Verderame, Mariailaria (International Journal of Zoology, 2014)
A crucial role in the maintenance of male reproductive functions is carried out by the androgen through its receptor in balance with the estrogen receptors (ERs). The distribution of the androgen receptor (AR) is well documented in the testis and in the reproductive tissues of mammals but the findings about the AR in nonmammalian vertebrates and in particular in reptiles are very scarce. Here by means of in situ hybridization (ISH) we investigated the AR expression along the epididymal channel (efferent ductules, corpus, and cauda) of Podarcis sicula during the mating and nonmating period. The results show that in this seasonal breeding species the AR expression pattern is always constant throughout the epididymis. The administration of estradiol-17β in the mating period does not affect the AR expression but inhibits the secretory activity of the epididymal corpus. To verify the expression pattern of ERs, we also conducted ISH investigations on adjacent sections with ERs probes. The findings suggest that AR induces the secretory activity in the epithelial cells of the epididymal corpus and confirm our previous results that showed the role of ERalpha (ERα) as switch off for the secretion of this compartment.